Adsorption Of Methylene Blue Onto Modified Factory Tea Waste: Batch And Fixed Bed Column - Nasuha, Norhaslinda (2011)
The aim of this work was to investigate the feasibility of chemically modified agricultural waste, namely factory tea waste (R-TW) for adsorption of methylene blue (MB) from aqueous solutions. The results revealed that modification of R-TW with sodium hydroxide (NaOH) and potassium hydroxide (KOH) which named NaOH-TW and KOH-TW respectively give the highest efficiencies for MB adsorption compared with other modification methods. R-TW, KOH-TW and NaOH-TW were characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and nitrogen adsorption/desorption isotherm analyses.